Isolation and Identification of Shigella Sonnei from Children with Diarrhea and Detection of the Most Important Virulence Factors - Hayfaa Rajab Alwan; Mohammed Nadhir Maaroof (Institute of Medico-legal Publications Pvt Ltd, 2021)
Some reports showed that the sensitivity of Shigella species to antibiotics changed dramatically over time due to the indiscriminate use of drugs.The Shigella strains became gradually resistant to most antimicrobials, which led to failure of treatment and increased mortality.This study was conducted in Tikrit city and included the isolated of Shigella sonnei from 530 stool samples were collected from children suffering from diarrhea during the period from March 2018 to March 2019.Stool samples taken from children aged 1-60 month.The study showed that all the fifteen isolates obtained were Shigella sonnei, meaning that the infection rate was 2.83% of the total number of patients.The age group from 49-60 months is the group most likely to be affected by Shigella.The results of determining some virulence factors indicated that all Shigella sonnei isolates possess the ability to form biofilms, and 93.3% of these isolates produce beta-lactamase.As for the ability of isolates to cause keratoconjunctivitis,the results showed that 80% of the isolates were positive for the sereny test, that is,it has the ability to cause the disease. The results of the study showed that all isolates were resistant to antibiotics Nalidixic acid and Co-trimoxazole, and 93.3% of the isolates were resistant to Penicillin.Antibiotics Chloramphenicol and Azithromycin showed a significant effect on Shigella isolates,as 93.3% of isolates were sensitive to these antibiotics.The antibiotic Ciprofloxacin showed an asymptotic inhibition to the antibiotics Chloramphenicol and Azithromycin, as the results showed that 86.6 isolates were sensitive to this antibiotic.Antibiotics of the third generation cephalosporins Cefotaxime and Ceftriaxone,showed convergent effects in their ability to inhibit Shigella sonnei isolates, as the results showed that the isolates were sensitive to the antibiotics at a rate of 73.4% and 80% respectively.The percentage of isolates sensitive to the antibiotics Amikacin and Tetracycline were 40% and 46.7% respectively.